Oscillation Results for BVPs of Even Order Nonlinear Neutral Partial Differential Equations (Journal of Nonlinear Modeling and Analysis, 2024)
A class of boundary value problems (BVPs) of even order neutralpartial functional differential equations with continuous distribution delay andnonlinear diffusion term are studied. By applying the integral average andRiccati's method, the high-dimensional oscillatory problems are changed intothe one-dimensional ones, and some new sufficient conditions are obtainedfor oscillation of all solutions of such boundary value problems under firstboundary condition. The results generalize and improve some results of thelatest literature.